The Effect of Parental Absence or Presence on Dental Anxiety of Pediatric Patients in Dental Clinic - Hamit Tunç (European Annals of Dental Sciences)

(untitled)
Purpose: The study aimed to evaluate effect of parental absence or presence on anxiety level of children in dental clinic.Materials and Methods: 130 children who 6-9 years old were randomly divided into two groups as absence of parents (PA) (n=65) and presence of parents (PP) (n=65). Before and after the dental procedures The Abeer Children Dental Anxiety Scale (ACDAS) was applied to all participants in both groups. All data were analysed with two sample t test and p value set at < .05 for significance level.Results: The mean age of participants was 6.9±1,18 years. The ACDAS score of PP on first visit was significantly lower than ACDAS score of PP on second visit (p<0.001). When comparing the mean ACDAS score of PA group on first and second visit, mean ACDAS score of PA group on second visit significantly lower than first visit (p<0.001). There were no significant differences between mean ACDAS score of both genders (p>0.05).Conclusions: According to results of current study, using of parental absence or presence technique in children who 6-9 years old is efficient method for developing to behaviours of children during the dental procedures such as composite restorations under local anaesthesia.